The Influence of Influencers Popularity, Online Customer Review and Advertising Exposure on Npure Purchase Interest on E-Commerce Shopee - Rosyada Setijawan, Amrina; Pradekso, Tandiyo; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Beauty and cosmetics products are the best-selling products right now. It is known that the cosmetics and beauty industry in Indonesia has increased from year to year and contributed 1.92% to gross domestic product (GDP) (Bisnis Indonesia, 2022. Skincare is one of the beauty products needed to keep skin healthy. Not only for women, now many men also use it. Until 2022, recorded skincare sales in Indonesia reached IDR 292.4 billion in the second quarter (Compas, 2022). NPure is a local skincare brand that was founded in 2017 with a campaign in the form of skincare products with natural ingredients. NPure also revealed that its products come from raw materials taken from farmers in Indonesia, which also supports the welfare of farmers in Indonesia. The existence of many skincare brands in the beauty and cosmetics category makes it necessary for NPure to implement strategies to attract more consumer purchase interest in skincare. This study aims to evaluate the marketing communication tools used by NPure and to find out is there any influence of influencers popularity, online customer review, and advertising exposure on NPure purchase interest. The hypotheses in this study are derived from theory used in this study is the Source of Attractiveness Model, Cognitive Response Approach theory and Advertising Exposure theory, with the sampling technique of non-probability sampling. The sample consists of 100 people with female and male characteristics that already know about NPure influencers popularity, NPure online customer review and NPure advertising. The results showed that the hypothesis about influencers popularity on purchase interest, online customer review on purchase interest and advertising exposure on purchase interest is accepted with a significance value of 0.000, indicating there is a significant influence on purchase intention.